Implikasi Pemberlakuan Undang-Undang Nomor 1 Tahun 2023 Tentang Kitab Undang-Undang Hukum Pidana Terhadap Pembaruan Politik Hukum Pidana Di Indonesia - Eka Fitri Lestari; Donly Calner Aruan; Meina Alvionita br Purba; Ismaidar Ismaidar; Abdul Rahman Maulana Siregar (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
The reform of Indonesia’s national criminal law through the enactment of Law Number 1 of 2023 on the Criminal Code (KUHP) represents a strategic effort to establish a legal system aligned with Pancasila, the 1945 Constitution, and societal developments. The new KUHP marks the end of the long-standing influence of the Dutch colonial criminal code and reflects a new direction in criminal law policy emphasizing the balance between legal certainty, justice, and utility. This study aims to analyze the implications of the new KUHP on the reform of Indonesia’s criminal law policy and to examine the challenges in its implementation. The research employs a normative legal method using statutory and conceptual approaches, supported by primary, secondary, and tertiary legal materials. The findings indicate that the new KUHP introduces fundamental changes, including the strengthening of a modern legality principle, recognition of living law, the development of restorative justice, reformulation of sentencing systems, and enhanced corporate criminal liability. Furthermore, it reflects efforts toward decolonizing criminal law and creating a more adaptive legal system in response to social, cultural, and technological changes. However, its implementation faces challenges such as regulatory harmonization, law enforcement readiness, public understanding, and potential differences in interpreting new legal norms. Therefore, strong synergy among the government, law enforcement agencies, academics, and society is essential to ensure effective and just criminal law reform.